2021
DOI: 10.1101/2021.02.11.430787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 variants B.1.351 and B.1.1.248: Escape from therapeutic antibodies and antibodies induced by infection and vaccination

Abstract: The global spread of SARS-CoV-2/COVID-19 is devastating health systems and economies worldwide. Recombinant or vaccine-induced neutralizing antibodies are used to combat the COVID-19 pandemic. However, recently emerged SARS-CoV-2 variants B.1.1.7 (UK), B.1.351 (South Africa) and B.1.1.248 (Brazil) harbor mutations in the viral spike (S) protein that may alter virus-host cell interactions and confer resistance to inhibitors and antibodies. Here, using pseudoparticles, we show that entry of UK, South Africa and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 44 publications
0
50
0
2
Order By: Relevance
“…Prior to this, while many distinct spike mutations had been observed, all circulating SARS-CoV-2 lineages were defined by small numbers of mutations. All of the 501Y lineages also have significantly altered phenotypes: increased human ACE2 receptor affinity (V1, V2 and V3) [9][10][11] , increased transmissibility (V1 and V2) [12][13][14] , increased capacity to overcome prior infection and/or vaccination-induced immunity (V2 and V3) [15][16][17][18][19] and associations with increased virulence (V1) 20 . Why did the heavily mutated 501Y lineages all arise on different continents at almost the same time?…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this, while many distinct spike mutations had been observed, all circulating SARS-CoV-2 lineages were defined by small numbers of mutations. All of the 501Y lineages also have significantly altered phenotypes: increased human ACE2 receptor affinity (V1, V2 and V3) [9][10][11] , increased transmissibility (V1 and V2) [12][13][14] , increased capacity to overcome prior infection and/or vaccination-induced immunity (V2 and V3) [15][16][17][18][19] and associations with increased virulence (V1) 20 . Why did the heavily mutated 501Y lineages all arise on different continents at almost the same time?…”
Section: Introductionmentioning
confidence: 99%
“…CoV-X2 is expected to be more resistant to viral escape compared to monoclonals. Indeed, we have shown that CoV-X2 binds and neutralizes mutants not recognized by its parental mAbs as well as variants of concern that recently emerged in United Kingdom 13 , South Africa 14 and Brazil 26 .…”
mentioning
confidence: 99%
“…During the second wave of the pandemic (end of 2020/early 2021), new SARS-CoV-2 variants emerged, subsequently replacing old variants [291]. Some of these second-wave Spike mutations seem to confer partial neutralization resistance, as measured in in vitro assays with convalescent or vaccine sera [292][293][294][295][296][297]. Available potent vaccines at optimal dosing can induce multiple times higher nAb titers than convalescent sera [293,[298][299][300] and might thus have a broader window to compensate for partial Ab escape.…”
Section: Sars-cov-2 Mutates On a Low But Constant Level Yielding Mutant Variants Over Timementioning
confidence: 99%